2011
DOI: 10.1002/ajim.20947
|View full text |Cite
|
Sign up to set email alerts
|

Trends in occupational airway diseases in german hairdressers: Frequency and causes

Abstract: The number of allergen- and irritant-induced cases of OAD in German hairdressers is still high. Exposure to known airway irritants is still occurring in spite of modification of the formulations. Continuous medical surveillance of hairdressers is recommended, in order to detect individual susceptibility, especially in apprentices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…In Germany, changes in recognized compensation claims for occupational obstructive airway diseases (OADs) were reported by causal agents from 1970 to 2005 [25]. Another German study [14] of confirmed compensation cases of OAD from 1998 to 2007 observed a decline in latex-induced OAD in healthcare workers and in allergen-induced OAD in hairdressers from 2003. In an occupational dermatology clinic database Victoria, Australia, there was an increase in incidence for OACD in hairdressers from 1999 to 2004 followed by a decline from to 2009, but no change in compensation claims over the same period [42].…”
Section: Trends In Occupational Allergy and Asthma By Exposure Or Occmentioning
confidence: 97%
See 1 more Smart Citation
“…In Germany, changes in recognized compensation claims for occupational obstructive airway diseases (OADs) were reported by causal agents from 1970 to 2005 [25]. Another German study [14] of confirmed compensation cases of OAD from 1998 to 2007 observed a decline in latex-induced OAD in healthcare workers and in allergen-induced OAD in hairdressers from 2003. In an occupational dermatology clinic database Victoria, Australia, there was an increase in incidence for OACD in hairdressers from 1999 to 2004 followed by a decline from to 2009, but no change in compensation claims over the same period [42].…”
Section: Trends In Occupational Allergy and Asthma By Exposure Or Occmentioning
confidence: 97%
“…In this review, we will first consider the trends in OAA over all exposures combined and then examine trends in OAA attributed to specific exposures, for example epoxy resins [13], or occupational sectors, for example hairdressers [14]. ].…”
Section: Trends In Occupational Allergy and Asthma Across All Exposuresmentioning
confidence: 99%
“…rhinitis (8), and asthma (9)(10)(11)(12). In these registry studies, the primary focus is on diagnosed cases of disease, and thereby conservative risk estimates of the actual occurrence are given.…”
mentioning
confidence: 99%
“…Few studies have focused in this subject, however, it should be considered in the assessment of exposure to nonvolatile substances in cosmetic products used in hairdressing 27 . On the other 21 hand, observations have revealed that for most workers, the use of gloves means wearing them principally during application of the mixture but not necessarily during other steps. Thus, they may declare that they use protective equipment when they only use them for one step.…”
Section: In Viewingmentioning
confidence: 98%
“…During application, hair dyes may be in contact with hairdressers' skin through dermal contact but, at the same time, they can be inhaled due to evaporation. 9,20,21 Professional practices also impact the degree of exposure. For example, the risk for hairdressers via dermal exposure seems to increase with the practice of unprotected wet work 23 .…”
Section: Introductionmentioning
confidence: 98%